International law, security, and military power : US and Brazilian perspectives - Hensel, Howard M.; Silva, Carlos Alberto Leite da (Justice, international law and global security, 2025)
This book contributes to our understanding and appreciation of the contemporary relevance of international humanitarian law and international human rights law by analyzing and assessing the foundational norms, principles, and provisions contained within these bodies. It also explores the ways in which they inform and condition military doctrine and the planning and the execution of military operations in the land, air, cyber, and space domains as perceived through the lens of two of the most important military establishments in the Western Hemisphere - the United States and Brazilian militaries. The expert contributors promote a better awareness and comparative understanding of the rapidly changing, diverse traditional and non-traditional challenges and demands of the 21st century. This volume will be useful to both scholars whose research focuses on international law and military professionals.